Resin composition, prepreg, laminated board and preparation method thereof
By chemically modifying the polyphenylene ether, the polyphenylene ether with reactive phthalene group-terminated polyphenylene ether and the introduction of a phenolphthalethyl group-containing polyarylene ether amine structure is formed to form a high-performance thermosetting resin, which solves the problem of insufficient performance of traditional polyphenylene ether resins. The laminate produced has excellent comprehensive performance.
Patent Information
- Application Number
- CN202411915442.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Traditional polyphenylene ether resins have shortcomings in glass transition temperature, initial thermal decomposition temperature, mechanical strength and solvent resistance, and cannot meet the high-performance needs of copper clad laminates.
By chemically modifying the polyphenylene ether, the reactive phthalene group-terminated polyphenylene ether is adopted, and a phenolphthalethyl group-containing polyarylene ether amine structure is introduced to form a high-performance thermosetting resin, which improves its glass transition temperature, initial thermal decomposition temperature, mechanical strength and flame retardant properties, while reducing dielectric constant and dielectric loss.
The obtained resin composition laminate has excellent properties such as high heat resistance, high modulus, intrinsic flame retardancy, low dielectric loss, and low water absorption, and meets the high performance needs of copper clad laminate.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resin compositions, and in particular to a resin composition, a prepreg, a laminate and a preparation method thereof. Background Art
[0002] As electronic circuits develop towards miniaturization, diversification, and high-density interconnection, higher requirements are placed on the performance of copper clad laminates. Compared with traditional epoxy resin-based copper clad laminates, new copper clad laminates must have higher glass transition temperature, high thermal decomposition temperature, flame retardancy, high modulus, low thermal expansion coefficient, and low dielectric constant and dielectric loss.
[0003] Poly (2,6-dimethyl-1,4-phenylene oxide), also known as polyphenylene ether, abbreviated as PPO in English, is a resin with low dielectric constant and dielectric loss, low thermal expansion coefficient and low water absorption, which can be used to prepare high-frequency and high-speed copper-clad laminates. However, as a thermoplastic resin, it has disadvantages such as low glass transition temperature, insufficient initial thermal decomposition temperature, poor mechanical strength and poor solvent resistance, which limit its further application.
[0004] To improve this situation, researchers chemically modified polyphenylene ether to make it have higher glass transition temperature, initial thermal decomposition temperature, low dielectric loss and low water absorption. However, its glass transition temperature and initial thermal decomposition temperature are still low and cannot meet the application requirements of copper clad laminates.
[0005] Therefore, the traditional technology still needs to be further improved. Summary of the invention
[0006] Based on this, one or more embodiments of the present application provide a resin composition, a prepreg, a laminate and a preparation method thereof. The laminate has high peel strength, high decomposition temperature, high elastic modulus, good flame retardancy and excellent comprehensive performance.
[0007] According to the first aspect of the present application, a resin composition is provided, comprising the following components, by mass: 40 to 100 parts of phthalonitrile-terminated polyphenylene ether, 10 to 40 parts of phenolphthalein-containing polyaryletheramine, and 10 to 60 parts of inorganic filler;
[0008] The structure of the phthalonitrile-terminated polyphenylene ether is shown in formula (I), and the structure of the phenolphthalein-containing polyaryletheramine is shown in formula (II):
[0009]
[0010]
[0011] Wherein, a, m and n are all positive integers, and Y is a C1-C3 alkylene group or a single bond.
[0012] In some embodiments, the resin composition satisfies at least one of the following characteristics:
[0013] (1) The mass fraction of the phthalonitrile-terminated polyphenylene ether is 40 to 60 parts;
[0014] (2) The mass fraction of the phenolphthalein-containing polyaryletheramine is 10 to 30 parts;
[0015] (3) The mass fraction of the inorganic filler is 30 to 60 parts.
[0016] In some embodiments, the inorganic filler includes one or more of zirconium vanadate, zirconium tungstate, hafnium tungstate, microcrystalline glass, eucryptite, silica, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc, aluminum oxide, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay and kaolin.
[0017] In some of the embodiments, the components of the resin composition further include one or more of a curing accelerator, a coupling agent, a toughening agent, and an organic solvent;
[0018] Optionally, the curing accelerator includes one or more of 4,4'-methylenebis(2-ethyl)aniline, 2,2'-diallylbisphenol A and anhydrous cupric chloride;
[0019] Optionally, the coupling agent includes one or more of KH-550 and KH-560.
[0020] According to a second aspect of the present application, a method for preparing the resin composition as described above is provided, comprising the following steps: mixing the components of the resin composition to obtain the resin composition.
[0021] In some embodiments, the method for preparing the phthalonitrile-terminated polyphenylene ether comprises the following steps:
[0022] The polyphenylene ether and 4-nitrophthalonitrile are mixed in a solvent and reacted at 50° C. to 60° C. for 10 h to 12 h to prepare the phthalonitrile-terminated polyphenylene ether.
[0023] In some embodiments, the preparation method of the phenolphthalein-containing polyaryletheramine comprises the following steps:
[0024] Phenolphthalein and 1,3-dichloro-2-nitrobenzene are mixed in a solvent and reacted at 180°C to obtain a nitro-containing polyaryletherketone;
[0025] The nitro-containing polyaryletherketone is mixed with cyclohexanone, glacial acetic acid and iron powder, and refluxed at 80° C. for 12 hours to prepare the phenolphthalein-containing polyaryletheramine.
[0026] According to a third aspect of the present application, a method for preparing a prepreg is provided, comprising the following steps:
[0027] The resin composition or the resin composition prepared by the method for preparing the resin composition is attached to the surface of the reinforcing material and semi-cured to obtain the prepreg.
[0028] In some embodiments, the semi-curing treatment is performed at a temperature of 150° C. to 250° C. for a time of 2 min to 10 min.
[0029] In some embodiments, the reinforcing material includes one or more of an inorganic fiber material and an organic fiber material;
[0030] Optionally, the inorganic fiber material includes one or more of glass fiber, carbon fiber, silicon carbide fiber and asbestos fiber;
[0031] Optionally, the organic fiber material includes one or more of nylon, ultra-high molecular weight polyethylene fiber, aramid fiber, polyimide fiber, polyester fiber and cotton fiber.
[0032] According to a fourth aspect of the present application, a prepreg is provided, which is prepared using the above-mentioned method for preparing the prepreg.
[0033] According to a fifth aspect of the present application, a method for preparing a laminate is provided, comprising the following steps:
[0034] The prepreg is subjected to vacuum hot pressing to prepare the laminate.
[0035] In some embodiments, the method for preparing the laminate satisfies at least one of the following features:
[0036] (1) The temperature of the vacuum hot pressing treatment is 150°C to 300°C;
[0037] (2) The pressure of the vacuum hot pressing treatment is 10 kgf / cm 2 ~30kgf / cm 2 ;
[0038] (3) The vacuum degree of the vacuum hot pressing treatment is less than 2 kPa;
[0039] (4) The vacuum hot pressing treatment time is 200 min to 400 min.
[0040] According to the sixth aspect of the present application, a laminate is provided, which is prepared by the above-mentioned method for preparing the laminate.
[0041] In some of these embodiments, one or both sides of the laminate are coated with metal foil.
[0042] Compared with the traditional technology, this application has the following beneficial effects:
[0043] The present application chemically modifies polyphenylene ether and uses reactive phthalonitrile groups to terminate polyphenylene ether, so that it forms phthalocyanine ring and triazine ring structures through the self-polymerization of phthalonitrile, and obtains high-performance thermosetting resin, which improves its glass transition temperature, initial thermal decomposition temperature, mechanical strength, flame retardant properties, etc. At the same time, the introduction of phenolphthalein-containing polyaryletheramine structure and phthalonitrile group copolymerization can further reduce the dielectric constant and dielectric loss of the resin composition and improve the elastic modulus. The laminated board made using the resin composition of the present application has excellent properties such as high heat resistance, high modulus, intrinsic flame retardancy, low dielectric loss, and low water absorption. DETAILED DESCRIPTION
[0044] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0046] In the present application, "alkylene" refers to a hydrocarbon group having two monovalent radical centers derived from an alkyl group by removing a hydrogen atom, which can be a saturated branched alkyl group or a saturated straight chain alkyl group. 1 ~C 9 "Alkylene" means that the alkyl portion contains 1 to 9 carbon atoms, each occurrence can be independently C 1 Alkylene, C 2 Alkylene, C 3 Alkylene, C 4 Alkylene, C 5 Alkylene, C 6 Alkylene, C 7 Alkylene, C 8 Alkylene or C9 Suitable examples include, but are not limited to, methylene (-CH 2 -), 1,1-ethyl (-CH(CH 3 )-), 1,2-ethyl (-CH 2 CH 2 -), 1,1-propyl (-CH(CH 2 CH 3 )-), 1,2-propyl (-CH 2 CH(CH 3 )-), 1,3-propyl (-CH 2 CH 2 CH 2 -) and 1,4-butyl (-CH 2 CH 2 CH 2 CH 2 -).
[0047] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0048] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0049] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0050] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0051] In a first aspect of the present application, a resin composition is provided, comprising the following components, by mass: 40 to 100 parts of phthalonitrile-terminated polyphenylene ether, 10 to 40 parts of phenolphthalein-containing polyaryletheramine, and 10 to 60 parts of inorganic filler;
[0052] The structure of the phthalonitrile-terminated polyphenylene ether is shown in formula (I), and the structure of the phenolphthalein-containing polyaryletheramine is shown in formula (II):
[0053]
[0054]
[0055] Wherein, a, m and n are all positive integers, and Y is a C1-C3 alkylene group or a combination.
[0056] The present application chemically modifies polyphenylene ether and uses reactive phthalonitrile groups to terminate polyphenylene ether, so that phthalocyanine ring and triazine ring structures are formed through the self-polymerization of phthalonitrile, thereby obtaining a high-performance thermosetting resin, and improving its glass transition temperature, initial thermal decomposition temperature, mechanical strength, flame retardant properties, etc.; in order to reduce the thermal curing temperature of the phthalonitrile group, a phenolphthalein-containing polyaryletheramine structure is introduced and copolymerized with it, which can further reduce the dielectric constant and dielectric loss of the resin composition and improve the elastic modulus.
[0057] It can be understood that when Y is directly bonded, it means that Y does not represent any group, and two adjacent benzene rings are directly bonded.
[0058] As an example, the mass fraction of the phthalonitrile-terminated polyphenylene ether can be 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts, 98 parts, 99 parts, 100 parts, 101 parts, 102 parts, 103 parts, 104 parts, 105 parts, 106 parts, 107 parts, 108 parts, 109 parts, 0, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, or any value within the range formed by any two of the above point values.
[0059] Furthermore, the mass fraction of the phthalonitrile-terminated polyphenylene ether is 40 parts to 60 parts; further, the mass fraction of the phthalonitrile-terminated polyphenylene ether is 40 parts to 50 parts.
[0060] As an example, the mass fraction of the phenolphthalein-containing polyaryletheramine can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 34 parts, 39 parts, 40 parts, or any value within the range formed by any two of the above point values.
[0061] Furthermore, the mass fraction of the phenolphthalein-containing polyaryletheramine is 10 parts to 30 parts; further, the mass fraction of the phenolphthalein-containing polyaryletheramine is 10 parts to 20 parts.
[0062] As an example, the mass fraction of the inorganic filler can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 34 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, or any value within the range formed by any two of the above points.
[0063] Furthermore, the mass fraction of the inorganic filler is 30 parts to 60 parts; furthermore, the mass fraction of the inorganic filler is 30 parts to 40 parts.
[0064] In some embodiments, the inorganic filler includes one or more of zirconium vanadate, zirconium tungstate, hafnium tungstate, microcrystalline glass, eucryptite, silica, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc, aluminum oxide, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay and kaolin.
[0065] Furthermore, the inorganic filler is selected from silicon dioxide; furthermore, the inorganic filler is selected from spherical silicon dioxide.
[0066] In some embodiments, the components of the resin composition further include one or more of a curing accelerator, a coupling agent, a toughening agent, and an organic solvent.
[0067] Further, the curing accelerator includes one or more of 4,4'-methylenebis(2-ethyl)aniline, 2,2'-diallylbisphenol A and anhydrous cupric chloride.
[0068] Among them, the CAS number of 4,4'-methylenebis(2-ethyl)aniline is 19900-65-3; the CAS number of 2,2'-diallylbisphenol A is 1745-89-7; and the CAS number of anhydrous cupric chloride is 7447-39-4.
[0069] Further, the coupling agent includes one or more of KH-550 and KH-560.
[0070] In some embodiments, the components of the resin composition further include a solvent.
[0071] Further, the solvent includes one or more of toluene and N,N-dimethylformamide. Further, the solvent includes toluene and N,N-dimethylformamide; further, the mass ratio of toluene to N,N-dimethylformamide is 1:1.
[0072] The present application adopts the resin composition prepared by the above-mentioned improved phthalonitrile-terminated polyphenylene ether and phenolphthalein-containing polyaryletheramine, and the prepared laminate has excellent comprehensive properties such as high peel strength, high decomposition temperature, high elastic modulus, good flame retardant properties, low dielectric constant, and low water absorption.
[0073] In a second aspect of the present application, a method for preparing the above-mentioned resin composition is provided, comprising the following steps:
[0074] The components of the above resin composition are mixed to prepare a resin composition.
[0075] In some embodiments, the method for preparing phthalonitrile-terminated polyphenylene ether comprises the following steps:
[0076] The polyphenylene ether and 4-nitrophthalonitrile are mixed in a solvent, and reacted at 50° C. to 60° C. for 10 h to 12 h to prepare the phthalonitrile-terminated polyphenylene ether.
[0077] In some embodiments, the method for preparing phthalonitrile-terminated polyphenylene ether comprises the following steps:
[0078] The dissolved polyphenylene ether is mixed with 4-nitrophthalonitrile, heated to 50°C-60°C in an oil bath, and reacted by high-speed stirring for 10h-12h to prepare phthalonitrile-terminated polyphenylene ether.
[0079] In some embodiments, the method for preparing phthalonitrile-terminated polyphenylene ether further comprises the following steps: after the reaction is completed, the reaction product is filtered to collect the precipitate; and the precipitate is sequentially washed and vacuum dried.
[0080] As an example, the reaction temperature can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, or any value within the range formed by any two of the above values. The reaction time can be 10h, 10.5h, 11h, 11.5h, 12h, or any value within the range formed by any two of the above values.
[0081] In some embodiments, the preparation method of the phenolphthalein-containing polyaryletheramine comprises the following steps:
[0082] Phenolphthalein and 1,3-dichloro-2-nitrobenzene are mixed in a solvent and reacted at 180°C to obtain a nitro-containing polyaryletherketone;
[0083] The nitro-containing polyaryletherketone was mixed with cyclohexanone, glacial acetic acid and iron powder, and refluxed at 80°C for 12 hours to prepare the phenolphthalein-containing polyaryletheramine.
[0084] In some embodiments, the preparation method of the phenolphthalein-containing polyaryletheramine comprises the following steps:
[0085] The dissolved 1,3-dichloro-2-nitrobenzene is added dropwise to the dissolved phenolphthalein, and the mixture is heated to 150°C in an oil bath for azeotropy for 3 hours, and the mixture is heated to 180°C for reaction until the product shows obvious pole climbing phenomenon, and a large amount of distilled water is added to quench the reaction, and the precipitate is collected; the precipitate is washed and vacuum dried to obtain a nitro-containing polyaryletherketone;
[0086] The intermediate product was dissolved in a mixed solvent of cyclohexanone and an appropriate amount of glacial acetic acid, and iron powder was added. After reflux at 80° C. for 12 hours, the obtained product was spread on diatomaceous earth and filtered to obtain an organic layer. The solvent was removed by rotary evaporation, and distilled water was added to wash the filtered precipitate. The precipitate was vacuum dried to constant weight to obtain a phenolphthalein-containing polyaryletheramine.
[0087] In a third aspect of the present application, a method for preparing a prepreg is provided, comprising the following steps:
[0088] The resin composition or the resin composition prepared by the method for preparing the resin composition is attached to the surface of the reinforcing material and semi-cured to obtain a prepreg.
[0089] In some embodiments, the semi-curing treatment is performed at a temperature of 150° C. to 250° C. for a time of 2 min to 10 min.
[0090] It can be understood that the method of covering the resin composition on the surface of the reinforcing material includes one or more of a dipping method, a padding method and a coating method.
[0091] As an example, the temperature of the semi-curing treatment can be 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, or any value within the range formed by any two of the above values. The time of the semi-curing treatment can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, or any value within the range formed by any two of the above values.
[0092] In some of these embodiments, the reinforcing material includes one or more of an inorganic fiber material and an organic fiber material.
[0093] Further, the inorganic fiber material includes one or more of glass fiber, carbon fiber, silicon carbide fiber and asbestos fiber. Further, the inorganic fiber material includes 2116 glass fiber cloth.
[0094] Further, the organic fiber material includes one or more of nylon, ultra-high molecular weight polyethylene fiber, aramid fiber, polyimide fiber, polyester fiber and cotton fiber.
[0095] In a fourth aspect of the present application, a prepreg is provided, which is prepared by the above-mentioned method for preparing the prepreg.
[0096] In a fifth aspect of the present application, a method for preparing a laminate is provided, comprising the following steps:
[0097] The prepreg is subjected to vacuum hot pressing to prepare a laminate.
[0098] In some embodiments, the number of prepregs is one or more.
[0099] Furthermore, before the plurality of prepregs are subjected to vacuum hot pressing, the method further includes the following step: stacking the plurality of prepregs.
[0100] In some embodiments, the temperature of the vacuum hot pressing treatment is 150°C~300°C; as an example, the temperature of the vacuum hot pressing treatment can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, or any value within the range formed by any two of the above point values.
[0101] In some embodiments, the pressure of the vacuum hot pressing process is 10 kgf / cm 2 ~30kgf / cm 2As an example, the pressure of vacuum hot pressing can be 10kgf / cm 2 、15kgf / cm 2 、20kgf / cm 2 、25kgf / cm 2 、30kgf / cm 2 , or any value within the range formed by any two of the above point values.
[0102] In some embodiments, the vacuum degree of vacuum hot pressing treatment is less than 2 kPa; as an example, the vacuum degree of vacuum hot pressing treatment can be: 1.8 kPa, 1.7 kPa, 1.5 kPa, 1.2 kPa, 1 kPa, 0.5 kPa, 0.2 kPa, 0.1 kPa, 0.05 kPa, 0.02 kPa, 0.01 kPa, or any value within the range formed by any two of the above point values.
[0103] In some embodiments, the time for vacuum hot pressing treatment is 200 min to 400 min. As an example, the time for vacuum hot pressing treatment can be 200 min, 220 min, 240 min, 260 min, 280 min, 300 min, 320 min, 340 min, 360 min, 380 min, 400 min, or any value within the range formed by any two of the above point values.
[0104] In a sixth aspect of the present application, a laminate is provided, which is prepared by the above-mentioned method for preparing the laminate.
[0105] In some of these embodiments, one or both sides of the laminate are coated with a metal foil.
[0106] In some examples, the metal foil includes a metal copper foil.
[0107] In some examples, the thickness of the metal foil is 3 μm to 70 μm; as an example, the thickness of the metal foil may be 3 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, or 70 μm.
[0108] The laminate comprising the above-mentioned resin composition of the present application has excellent comprehensive properties such as high peel strength, high decomposition temperature, high elastic modulus, good flame retardancy, low dielectric constant, and low water absorption.
[0109] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0110] The sources and models of some raw materials used in Examples 1 to 5 and Comparative Examples 1 to 3 of the present application are as follows.
[0111] Polyphenylene ether was purchased from SABIC, model SA-90; methacrylate-terminated polyphenylene ether was purchased from SABIC, model SA9000; 4-nitrophthalonitrile was purchased from INOKE, analytical grade; phenolphthalein was purchased from INOKE, analytical grade; 1,3-dichloro-2-nitrobenzene was purchased from INOKE, analytical grade; 1,3-dichlorobenzene was purchased from INOKE, analytical grade; anhydrous potassium carbonate was purchased from Aladdin, analytical grade; glacial acetic acid was purchased from INOKE, analytical grade; iron powder was purchased from Aladdin, analytical grade; spherical silica was purchased from Yaduma, model SC6500-SXD.
[0112] Example 1
[0113] (1) Preparation of phthalonitrile-terminated polyphenylene ether resin: Weigh polyphenylene ether SA90 (0.1 mol, 160 g) into a three-necked flask, add 600 mL of N,N-dimethylformamide and stir to completely dissolve it, then add anhydrous potassium carbonate (0.1 mol, 13.82 g) and 4-nitrophthalonitrile (0.11 mol, 19.04 g), keep the oil bath heated at 50°C, and stir at high speed to react for 12 h; after the reaction is completed, add deionized water and filter to collect the precipitate, then wash it with deionized water and ethyl acetate several times, respectively, and dry the obtained product in a vacuum oven at 80°C to constant weight to obtain phthalonitrile-terminated polyphenylene ether resin.
[0114] (2) Preparation of polyaryletheramine containing phenolphthalein: Phenolphthalein (0.3 mol, 95.5 g) was weighed and dissolved in 200 mL of a mixed solution of N-methylpyrrolidone and toluene (mass ratio of 3:1), and then anhydrous potassium carbonate (0.4 mol, 55.28 g) was added and stirred at high speed at room temperature; 1,3-dichloro-2-nitrobenzene (0.305 mol, 58.56 g) was dissolved in 50 mL The mixture is prepared from N-methylpyrrolidone and toluene, and then a solution containing 1,3-dichloro-2-nitrobenzene is added dropwise to the mixed solution. After the addition is completed, the mixture is heated in an oil bath at 150°C for azeotropic reaction for 3 hours to evaporate water and toluene, and then the temperature is raised to 180°C to react until the product shows obvious climbing phenomenon, a large amount of distilled water is added to quench the reaction, the precipitate is collected, and then washed with anhydrous ethanol and deionized water for several times, respectively, and dried in a vacuum oven at 100°C to constant weight to obtain an intermediate product, a nitro-containing polyaryletherketone; the intermediate product is dissolved in a mixed solvent of cyclohexanone and an appropriate amount of glacial acetic acid, iron powder (5eq) is added, and after refluxing at 80°C for 12 hours, the obtained product is spread on diatomaceous earth and filtered to obtain an organic layer, the solvent is removed by rotary evaporation, distilled water is added to wash the filtered precipitate, and the precipitate is dried in a vacuum oven at 80°C to constant weight to obtain a phenolphthalein-containing polyaryletheramine.
[0115] (3) 55 parts of the phthalonitrile-terminated polyphenylene ether resin prepared in step (1) and 5 parts of the phenolphthalein-containing polyaryletheramine prepared in step (2) were dissolved in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein the mass ratio of toluene to N,N-dimethylformamide was 1:1. Under stirring conditions, 40 parts of spherical silica were added, and stirring was continued to obtain a uniform glue solution, i.e., a resin composition.
[0116] (4) 2116 glass fiber cloth (basis weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 210°C for 3 min to obtain a prepreg with a resin content of 50%.
[0117] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 280℃ for 3h.
[0118] Example 2
[0119] The method is basically the same as Example 1, except that steps (3) to (5) are different, and the other steps and parameters are consistent with Example 1.
[0120] (3) Take 50 parts of the phthalonitrile-terminated polyphenylene ether resin prepared in step (1) and 10 parts of the phenolphthalein-containing polyaryletheramine prepared in step (2), and dissolve them in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein the mass ratio of toluene to N,N-dimethylformamide is 1:1. Under stirring conditions, 40 parts of spherical silica are added, and stirring is continued to obtain a uniform glue solution, i.e., a resin composition.
[0121] (4) 2116 glass fiber cloth (basis weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 210°C for 2 min to obtain a prepreg with a resin content of 50%.
[0122] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 260℃ for 3h.
[0123] Example 3
[0124] The method is basically the same as Example 1, except that steps (3) to (5) are different, and the other steps and parameters are consistent with Example 1.
[0125] (3) 45 parts of the phthalonitrile-terminated polyphenylene ether resin prepared in step (1) and 15 parts of the phenolphthalein-containing polyaryletheramine prepared in step (2) are dissolved in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein the mass ratio of toluene to N,N-dimethylformamide is 1:1. Under stirring conditions, 40 parts of spherical silica are added, and stirring is continued to obtain a uniform glue solution, i.e., a resin composition.
[0126] (4) 2116 glass fiber cloth (basis weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 200°C for 2 min to obtain a prepreg with a resin content of 50%.
[0127] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 260℃ for 3h.
[0128] Example 4
[0129] The method is basically the same as Example 1, except that steps (3) to (5) are different, and the other steps and parameters are consistent with Example 1.
[0130] (3) 40 parts of the phthalonitrile-terminated polyphenylene ether resin prepared in step (1) and 20 parts of the phenolphthalein-containing polyaryletheramine prepared in step (2) are dissolved in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein the mass ratio of toluene to N,N-dimethylformamide is 1:1. Under stirring conditions, 40 parts of spherical silica are added, and stirring is continued to obtain a uniform glue solution, i.e., a resin composition.
[0131] (4) 2116 glass fiber cloth (basis weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 180°C for 2 min to obtain a prepreg with a resin content of 50%.
[0132] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 240℃ for 3h.
[0133] Example 5
[0134] The method is basically the same as Example 1, except that steps (3) to (5) are different, and the other steps and parameters are consistent with Example 1.
[0135] (3) 30 parts of the phthalonitrile-terminated polyphenylene ether resin prepared in step (1) and 30 parts of the phenolphthalein-containing polyaryletheramine prepared in step (2) are dissolved in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein the mass ratio of toluene to N,N-dimethylformamide is 1:1. Under stirring conditions, 40 parts of spherical silica are added, and stirring is continued to obtain a uniform glue solution, i.e., a resin composition.
[0136] (4) 2116 glass fiber cloth (basis weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 180°C for 2 min to obtain a prepreg with a resin content of 50%.
[0137] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 240℃ for 3h.
[0138] Comparative Example 1
[0139] The method is basically the same as Example 1, except that steps (3) to (5) are different, and the other steps and parameters are consistent with Example 1.
[0140] (3) 60 parts of the phthalonitrile-terminated polyphenylene ether resin prepared in step (1) were dissolved in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein toluene and N,N-dimethylformamide were mixed in a mass ratio of 1:1. Under stirring conditions, 40 parts of spherical silica were added, and stirring was continued to obtain a uniform glue solution, i.e., a phthalonitrile-terminated polyphenylene ether resin composition.
[0141] (4) 2116 glass fiber cloth (basis weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 210°C for 3 min to obtain a prepreg with a resin content of 50%.
[0142] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 280℃ for 3h.
[0143] Comparative Example 2
[0144] (1) Providing methacrylate-terminated polyphenylene ether resin: purchased from SABIC, model number SA9000.
[0145] (2) The steps for preparing the polyaryletheramine containing phenolphthalein groups are the same as those in Example 1.
[0146] (3) 30 parts of the methacrylate-terminated polyphenylene ether resin prepared in step (1) and 30 parts of the phenolphthalein-containing polyaryletheramine prepared in step (2) are dissolved in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein the mass ratio of toluene to N,N-dimethylformamide is 1:1. Under stirring conditions, 40 parts of spherical silica are added, and stirring is continued to obtain a uniform glue solution, i.e., a resin composition.
[0147] (4) 2116 glass fiber cloth (basic weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 180°C for 3 min to obtain a prepreg with a resin content of 50%.
[0148] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 240℃ for 3h.
[0149] Comparative Example 3
[0150] (1) The steps for preparing phthalonitrile-terminated polyphenylene ether are the same as those in Example 1.
[0151] (2) Preparation of poly(aryletherketone) containing phenolphthalein: Phenolphthalein (0.3 mol, 95.5 g) was weighed and dissolved in a mixed solution of 200 mL of N-methylpyrrolidone and toluene (mass ratio: 3:1), and then anhydrous potassium carbonate (0.4 mol, 55.28 g) was added and stirred at room temperature at high speed; 1,3-dichlorobenzene (0.305 mol, 44.835 g) was dissolved in a mixed solution of 50 mL of N-methylpyrrolidone and toluene, and then the solution containing 1,3-dichlorobenzene was added dropwise to the mixed solution. After the addition was completed, the mixture was heated in an oil bath at 150°C for azeotropic reaction for 3 h to evaporate water and toluene, and then the temperature was raised to 180°C to react until the product showed obvious pole climbing phenomenon, and a large amount of distilled water was added to quench the reaction, and the precipitate was collected and then washed with anhydrous ethanol and deionized water for several times, respectively, and dried in a vacuum oven at 100°C to constant weight to obtain poly(aryletherketone) containing phenolphthalein.
[0152] (3) 30 parts of the phthalonitrile-terminated polyphenylene ether resin prepared in step (1) and 30 parts of the phenolphthalein-containing polyaryletherketone prepared in step (2) are dissolved in a mixed solvent of 140 parts of toluene and N,N-dimethylformamide, wherein the mass ratio of toluene to N,N-dimethylformamide is 1:1. Under stirring conditions, 40 parts of spherical silica are added, and stirring is continued to obtain a uniform glue solution, i.e., a resin composition.
[0153] (4) 2116 glass fiber cloth (basis weight 105 g / m²) was impregnated with the above resin composition and baked in a hot air circulation oven at 210°C for 3 min to obtain a prepreg with a resin content of 50%.
[0154] (5) 6 sheets of the above-mentioned prepreg were stacked, and a sheet of electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stacked body. The stacked body was placed in a programmable temperature and pressure controlled vacuum press and heated at 30 kgf / cm2 in a vacuum state. 2 Under pressure, a 0.6mm thick copper-clad laminate was produced after curing at 280℃ for 3h.
[0155] The compositions and proportions of the resin compositions in the above Examples 1 to 5 and Comparative Examples 1 to 3 are shown in the following table.
[0156] Table 1
[0157]
[0158] The copper clad laminates prepared in the above examples and comparative examples were tested for performance, and the test results are shown in Table 2.
[0159] The test method for peel strength refers to Section 2.4.8 of the IPC-TM-650 standard; the glass transition temperature (Tg) refers to Section 2.4.25D of the IPC-TM650 standard; the thermal decomposition temperature (Td) refers to Section 2.4.24.6 of the IPC-TM650 standard; the elastic modulus refers to the GB / T 22315-2008 standard; the water absorption refers to the IPC-TM650 2.6.2.1 standard; the dielectric constant / dielectric loss factor (Dk / Df) refers to the IPC-TM650 2.5.5.2 standard; the flame retardant grade refers to the IPC-TM650 2.3.10 standard.
[0160] Table 2
[0161]
[0162] It can be seen from the above table that the peel strength of the copper clad laminates prepared in Examples 1 to 5 is ≥5.2lb / in; the glass transition temperature is ≥320°C; the thermal decomposition temperature is ≥462°C; the dielectric constant is ≤3.42, the dielectric loss factor is ≤0.006; the flame retardant grade is V0; and the water absorption rate is ≤0.08%; it can be seen that the copper clad laminates prepared in this application have good peel strength, heat resistance, dielectric properties, flame retardant grade and water absorption rate.
[0163] In Comparative Example 1, no phenolphthalein-containing polyaryletheramine was added, and the heat resistance of the copper-clad laminate thus obtained was significantly reduced, and the dielectric constant was relatively high; in Comparative Example 2, the phthalonitrile-terminated polyphenylene ether was replaced with methacrylate-terminated polyphenylene ether, and the peel strength of the copper-clad laminate finally obtained was slightly reduced, and the heat resistance and elastic modulus were significantly reduced; in Comparative Example 3, the phenolphthalein-containing polyaryletheramine was replaced with a phenolphthalein-containing polyaryletherketone, and the peel strength, heat resistance and elastic modulus of the copper-clad laminate finally obtained were significantly reduced; and the dielectric constant was relatively high, indicating that the phenolphthalein-containing polyaryletheramine can effectively reduce the dielectric constant of the copper-clad laminate.
[0164] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0165] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A resin composition, characterized in that The composition comprises the following components by weight: 40 to 100 parts of phthalonitrile-terminated polyphenylene ether, 10 to 40 parts of phenolphthalein-containing polyaryletheramine and 10 to 60 parts of inorganic filler; The structure of the phthalonitrile-terminated polyphenylene ether is shown in formula (I), and the structure of the phenolphthalein-containing polyaryletheramine is shown in formula (II): Wherein, a, m and n are all positive integers, and Y is a C1-C3 alkylene group or a single bond.
2. The resin composition according to claim 1, characterized in that The resin composition satisfies at least one of the following characteristics: (1) The mass fraction of the phthalonitrile-terminated polyphenylene ether is 40 to 60 parts; (2) The mass fraction of the phenolphthalein-containing polyaryletheramine is 10 to 30 parts; (3) The mass fraction of the inorganic filler is 30 to 60 parts.
3. The resin composition according to any one of claims 1 to 2, characterized in that The inorganic filler includes one or more of zirconium vanadate, zirconium tungstate, hafnium tungstate, microcrystalline glass, eucryptite, silicon dioxide, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc, aluminum oxide, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay and kaolin.
4. The resin composition according to any one of claims 1 to 2, characterized in that The components of the resin composition also include one or more of a curing accelerator, a coupling agent, a toughening agent and an organic solvent; Optionally, the curing accelerator includes one or more of 4,4'-methylenebis(2-ethyl)aniline, 2,2'-diallylbisphenol A and anhydrous cupric chloride; Optionally, the coupling agent includes one or more of KH-550 and KH-560.
5. A method for preparing a resin composition according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the components of the resin composition to obtain the resin composition.
6. The method for preparing the resin composition according to claim 5, characterized in that: The preparation method of the phthalonitrile-terminated polyphenylene ether comprises the following steps: The polyphenylene ether and 4-nitrophthalonitrile are mixed in a solvent and reacted at 50° C. to 60° C. for 10 h to 12 h to prepare the phthalonitrile-terminated polyphenylene ether.
7. The method for preparing the resin composition according to claim 5, characterized in that: The preparation method of the phenolphthalein-containing polyaryletheramine comprises the following steps: Phenolphthalein and 1,3-dichloro-2-nitrobenzene are mixed in a solvent and reacted at 180°C to obtain a nitro-containing polyaryletherketone; The nitro-containing polyaryletherketone is mixed with cyclohexanone, glacial acetic acid and iron powder, and refluxed at 80° C. for 12 hours to prepare the phenolphthalein-containing polyaryletheramine.
8. A method for preparing a prepreg, characterized in that: The following steps are involved: The prepreg is prepared by attaching the resin composition according to any one of claims 1 to 4 or the resin composition prepared by the method for preparing the resin composition according to any one of claims 5 to 7 to the surface of the reinforcing material and performing a semi-curing treatment.
9. The method for preparing a prepreg according to claim 8, characterized in that: The temperature of the semi-curing treatment is 150° C. to 250° C., and the time is 2 min to 10 min.
10. The method for preparing a prepreg according to claim 8, characterized in that: The reinforcing material comprises one or more of an inorganic fiber material and an organic fiber material; Optionally, the inorganic fiber material includes one or more of glass fiber, carbon fiber, silicon carbide fiber and asbestos fiber; Optionally, the organic fiber material includes one or more of nylon, ultra-high molecular weight polyethylene fiber, aramid fiber, polyimide fiber, polyester fiber and cotton fiber.
11. A prepreg, characterized in that: The prepreg is prepared by the method for preparing the prepreg according to any one of claims 8 to 10.
12. A method for preparing a laminate, characterized in that: The following steps are involved: The prepreg according to claim 11 is subjected to vacuum hot pressing to prepare the laminate.
13. The method for preparing a laminate according to claim 12, characterized in that: The method for preparing the laminate meets at least one of the following characteristics: (1) The temperature of the vacuum hot pressing treatment is 150°C to 300°C; (2) The pressure of the vacuum hot pressing treatment is 10 kgf / cm 2 ~30kgf / cm 2 ; (3) The vacuum degree of the vacuum hot pressing treatment is less than 2 kPa; (4) The vacuum hot pressing treatment time is 200 min to 400 min.
14. A laminated board, characterized in that: The laminate is prepared by the method for preparing the laminate according to any one of claims 12 to 13.
15. The laminate according to claim 14, characterized in that The laminate is coated with metal foil on one or both sides.
Citation Information
Patent Citations
Phthalonitrile-terminated polyphenyl ether and preparation method and application thereof
CN112552510A
Modified polyphenyl ether composition as well as prepreg and laminated board prepared from modified polyphenyl ether composition
CN116003986A
Preparation method of functionalized oligomeric PPO modified phthalonitrile resin
CN116606548A
Inorganic material of high dielectric constant, and high dielectric constant composite material using the same
JP2005109316A
Radiation-sensitive resin composition, insulation film, method for forming the same film and display element
JP2016109855A
Cited By
High-modulus and high-toughness bismaleimide resin composition, prepreg preparation method and application
CN120775380A